Aplicações de uma formulação acurada e convergente para simular a condução de calor transiente em material anisotrópico no contexto de usinagem com laser para reutilização de pás de turbinas eólicas - Santos, Hygor Mathaeus Afonso (2024)
The search for a sustainable and economically viable destination for reusing blades used in wind generation is a reason for discussion and research around the world. They are made of composite materials, usually fiber reinforced polymers (FRP). Often the destination found requires the machining of this material, which is done through cuts using a laser. Due to the characteristics of the material, it is necessary to know how heat transfer occurs in an anisotropic environment, so that heat from the laser can be controlled and spread throughout the adjacent region, called the material's thermally affected zone (HAZ). Numerical simulation is a very attractive tool for understanding this process. This work aims to use it, applying two Finite Volume Method approaches to evaluate the ZTA, namely the Multipoint Flow Approximation (MPFA) and the Two-Point Flow Approximation (TPFA). The first is more suitable for working with materials in an anisotropic environment, while the second is not capable of generating an accurate solution depending on the anisotropy configuration considered. Two cases were evaluated, one being a reference where the methods converged with the analyzed analytical solution, and the case of the laser on the wind blade, which had its conclusion based on the previous benchmark case.